Quaternary Complexes Modified from pDNA and Poly‐l‐Lysine Complexes to Enhance pH‐Buffering Effect and Suppress Cytotoxicity. Issue 4 (4th February 2015) - Kodama, Yukinobu; Yatsugi, Yuiko; Kitahara, Takashi; Kurosaki, Tomoaki; Egashira, Kanoko; Nakashima, Mikiro; Muro, Takahiro; Nakagawa, Hiroo; Higuchi, Norihide; Nakamura, Tadahiro; Sasaki, Hitoshi
<x xml:space="preserve">Abstract</x> We developed a modified complex of pDNA and poly‐l‐lysine (PLL) by the addition of poly‐l‐histidine (PLH) and γ‐polyglutamic acid (γ‐PGA) to enhance its pH‐buffering effect and suppress cytotoxicity. The binary and ternary complexes of pDNA with PLL or/and PLH showed particle sizes of approximately 52–76 nm with cationic surface charge. The ternary complexes showed much higher gene expression than the binary complexes with PLL. The mixed solution of PLL and PLH showed higher buffering capacity than PLL solution. The high gene expression of ternary complexes was reduced by bafilomycin A1. These results indicated the addition of PLH to PLL complexes promoted endosomal escape by enhancing the pH‐buffering effect. The binary and ternary complexes showed cytotoxicity and blood agglutination because of their cationic surface charge. We therefore developed quaternary complexes by the addition of anionic γ‐PGA, which was reported to decrease the toxicity of cationic complexes. In fact, quaternary complexes showed no cytotoxicity and blood agglutination. Also, quaternary complexes showed higher gene expression than ternary complexes regardless of their anionic surface charge. Quaternary complexes showed selectively high gene expression in the spleen after their intravenous administration. Thus, we successfully developed the quaternary complexes with high gene expression and no toxicity. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1470–1477, 2015